The prospective role of matrix metalloproteinase-2/9 and transforming growth factor beta 1 in accelerating the progression of hepatocellular carcinoma - Chen, Gang; Qin, Gui-hui; Dang, Yi-wu; Yang, Jie (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
Hepatocellular carcinoma (HCC) related to cirrhosis is one of the most important health issues worldwide. The pathogenesis of cirrhosis is a result of chronic liver disease (CLD), which is characterized by an excessive accumulation of extracellular matrix (ECM) protein. The matrix metalloproteinases (MMPs) such as MMP-1, 2, 8, 9 and transforming growth factor beta 1 (TGF-β1) play important roles in the progression in CLD and HCC (1,2). The comment of Dr. Feitelson on our paper of which the title was “Reciprocal activation between MMP-8 and TGF-β1 stimulates EMT and malignant progression of hepatocellular carcinoma” in Cancer Letters (3) highlighted that the reciprocal activation between MMP-8 and TGF-β1 could be the target to delay or prevent the development of cirrhosis and/or HCC (4).